Pengaruh Kompetensi, Kompensasi Dan Disiplin Kerja Terhadap Kinerja Pegawai Non ASN (Study Pada Badan Pengembangan Sumber Daya Manusia Daerah (BPSDMD) Provinsi Jawa Tengah) - Nevanggi Wenti Ningrum; Haryani Haryani (Jurnal Ekonomi Manajemen Akuntansi, 2022)
This study aims to analyze "The Influence of Competence, Compensation, and Work Discipline on the Performance of Non ASN Employees (Study of the Regional Human Resource Development Agency (BPSDMD) of Central Java Province)". Methods of data collection using a questionnaire. The sampling technique used random sampling technique. A sample of 71 respondents were employees at the Regional Human Resources Development Agency (BPSDMD) of Central Java Province. Based on the results of testing the competency variable has a positive effect on employee performance. This is shown by the value of t count is greater than t table, namely 2.335 > 1.667 with a sig value. 0.023 > 0.05 and the regression coefficient (β1) is positive at 0.271 which means that the higher the employee's competency, the higher the employee's performance. So the hypothesis is proven. The compensation variable has a positive effect on employee performance. This is shown by the value of t count is greater than t table, namely 3.613 > 1.667, with a sig. of 0.001 <0.05 and the regression coefficient (β2) is positive at 0.411 which means that the more satisfying the compensation given, the higher the employee's performance. So the hypothesis is proven. While the work discipline variable has a positive effect on employee performance. This is shown by the greater t-count value of t-table, namely 2.548 > 1.667, with a sig. 0.013 < 0.05 and the regression coefficient (β3) is positive at 0.285 which means that the higher the employee's work discipline, the higher the employee's performance. So the hypothesis is proven.